The Effect of Self-Compassion on Loneliness in Early Adulthood in Makassar City - Suriana, Suriana; Rifani, Rohmah (Polteknik Ilmu Pemasyarakatan, 2024)
Loneliness is one of the problems felt by individuals who are entering the early adult phase. Individuals who feel lonely have a negative view not only of themselves but also of other people that have an impact on their social life. This research has not been widely carried out in Makassar City. This study aims to determine whether there is an effect of self-compassion on loneliness in early adulthood in Makassar City. This study used a quantitative method with a sample collection technique using an incidental sampling technique with a total of 286 respondents in Makassar City students with an age range of 18-26 years. The research data was obtained using the UCLA Loneliness and the Self-Compassion Scale. The results of simple linear regression analysis using SPSS 25 for windows obtained a significance value of 0.000 (p <0.05) and a coefficient of determination r² = 0.146 which means that self-compassion has an influence on the loneliness variable of 14.6%. The results of this study indicate that there is an effect of self-compassion on loneliness in early adulthood in Makassar City.